Performing qualitative cross-cultural research - Liamputtong, Pranee 1955- (Cambridge University Press, 2010)
Cross-cultural research is rife with ethical and methodological challenges but, despite the increased demand for such research, discussions on 'culturally sensitive methodologies' are still largely neglected. Consequently, researchers often find themselves faced with difficulties but lack information on how to deal with them. This text provides an in-depth discussion on how to perform qualitative research in cross-cultural contexts with an emphasis on a more ethical, sensible and responsible approach. Pranee Liamputtong suggests culturally sensitive and appropriate research methods that would work well with cultural groups. She offers thought-provoking perspectives and diverse cultural examples which will be of value to both novice and experienced cross-cultural researchers. Throughout the volume there are references to the excellent work of many cross-cultural researchers who have paved the way in different social and cultural settings